2017
DOI: 10.1108/rpj-08-2014-0101
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of direct 3D sand printing process for the production of sand cast mould tools

Abstract: The Metal casting industry is in recovery phase after the economic crisis in 2008, customer demand continues to increase, with 98.6 million metric tons cast in 2011. Traditional ferrous and non-ferrous casting techniques require one shot or permanent moulds which require tooling to be produced. Tooling particularly for developmental projects can be costly and take valuable time to produce. Additive manufacturing has been used to manufacture complex sand patterns for metal sand casting using laser sintering and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…The properties of sand moulds produced by the 3D printers can be controlled by numerous factors during the printing and or curing cycle (for phenolic or ZCast ® moulds). These properties are affected by the characteristics of the sand, the concentration and the type of binder and activator, printing speed (powder recoating speed) [17], job-box co-ordinate and build-orientation of the specimen printed [17,23], and layer [8,24] thickness. It has been found that decreasing the layer thickness and increasing the binder saturation improves the tensile strength but reduces the surface quality [24].…”
Section: Mould Properties and Their Effect On The Cast Metalmentioning
confidence: 99%
“…The properties of sand moulds produced by the 3D printers can be controlled by numerous factors during the printing and or curing cycle (for phenolic or ZCast ® moulds). These properties are affected by the characteristics of the sand, the concentration and the type of binder and activator, printing speed (powder recoating speed) [17], job-box co-ordinate and build-orientation of the specimen printed [17,23], and layer [8,24] thickness. It has been found that decreasing the layer thickness and increasing the binder saturation improves the tensile strength but reduces the surface quality [24].…”
Section: Mould Properties and Their Effect On The Cast Metalmentioning
confidence: 99%
“…The particles used in this study are generally relatively coarse, with the particle size of about 70-100 mesh [9] , while the metal powder mentioned above is generally relatively fine. Because the spacing caused by large particles will affect the final recognition accuracy, the finer the particles, generally speaking, the better the recognition efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The green body could then be postprocessed by pre-heating/sintering, infiltration and baking. Common applications of binder jet printing include: investment casting of metal parts (Utela et al, 2008;Hackney and Wooldridge, 2017;Paasi, 2021) especially for rapid prototyping of component designs; investigating rock mechanics with complex micro-and macro-geometries (Fereshtenejad and Song, 2016); fabrication of ceramics (Maleksaeedi et al, 2014), including scaffolds and grafts for ceramic biomaterials (Mandal and Basu, 2018;Zhang et al, 2014); and building and infrastructure construction elements using locally sourced cementitious materials (Shakor et al, 2019;Tay et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With such a wide range of end-uses of binder jet printing and a growing list of available powder materials, particle dimensions and bonding materials, mechanical and thermo-physical properties of the prints are becoming essential design parameters. In most applications, the functional printed elements must provide adequate mechanical strength, gas permeability, resistance to deformation by heat and reusability/ recyclability (Hackney and Wooldridge, 2017). The mechanical and thermophysical properties of the 3D-printed samples, in addition to print quality, can be tuned by the material selection, particle dimensions, printing parameters and post-processing techniques (Snelling et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation